Expressive Spaces in Digital 3D Cinema - Weetch, Owen.; SpringerLink (Online service) (London : Palgrave Macmillan UK(Imprint), 2016)
This book puts forward a more considered perspective on 3D, which is often seen as a distracting gimmick at odds with artful cinematic storytelling. Owen Weetch looks at how stereography brings added significance and expressivity to individual films that all showcase remarkable uses of the format. Avatar, Gravity, The Hole, The Great Gatsby and Frozen all demonstrate that stereography is a rich and sophisticated process that has the potential to bring extra meaning to a film's narrative and themes. Through close reading of these five very different examples, Expressive Spaces in Digital 3D Cinema shows how being sensitive to stereographic manipulation can nuance and enrich the critical appreciation of stereoscopic films. It demonstrates that the expressive placement of characters and objects within 3D film worlds can construct meaning in ways that are unavailable to 'flat' cinema.
List of Figures -- Acknowledgements -- Introduction: The Expressivity of Space -- 1. 'I See You': Avatar, Narrative Spectacle and Accentuating Continuity -- 2. 'You're Going to Make It': Ride Alignment and the Mastery of Stereographic Space in Gravity -- 3. 'You Only Looked that Way Because I was Little': Spaces of Terror and Reaching Maturity in The Hole -- 4. 'There's an Ocean in the Way': Written Words, Unreachability and Competing Testimonies in The Great Gatsby -- 5. 'Against the Wall': Frozen's Expressive Planarity, Attempts to Connect and Ambivalent Utopias -- Conclusion: A Special Plea for Off-the-Screen Space -- Glossary of Stereoscopic Terms -- Notes -- Bibliography -- .
Keywords: Motion pictures and television; Animated films; Screen Studies; Film Theory